Audit committee characteristics and environmental disclosure practices: Insights from Malaysian listed firms - Razali, Mohd Waliuddin Mohd; Fauzan, Nurra Farisha; Joseph, Corina; Yau, Damien Lee Iung; Hassan, Nurul Asyikin (Edelweiss Applied Science and Technology, 2025)
Audit committee has crucial roles in enhancing organizational practices including disclosure. This study's objective is to examine the relationship between audit committee characteristics and environmental disclosure, using agency and legitimacy theories. A sample of 380 Malaysian firms from 2020 to 2021 was analysed, with data from annual reports and market capitalization from the Orbis database. The panel regression was used to achieve the objective of this study. Results show that audit committee expertise has a significant positive relationship with environmental disclosure. Skilled members with sustainability knowledge enhance transparency, build stakeholder confidence, strengthen corporate reputation, and align practices with global sustainability goals. Expanding research in this area can further enhance understanding of how audit committees contribute to environmental practices and long-term value creation.